An Investigation to the Abrasive Wear in Pipes Used for Oil Industry (Journal of Engineering, 2013)
The work reported in this study focusing on the abrasive wear behavior for three types of pipes used in oil industries (Carbone steel, Alloy steel and Stainless steel) using a wear apparatus for dry and wet tests, manufactured according to ASTM G65. Silica sand with hardness (1000-1100) HV was used as abrasive material. The abrasive wear of these pipes has been measured experimentally by measuring the wear rate for each case under different sliding speeds, applied loads, and sand conditions (dry or wet). All tests have been conducted using sand of particle size (200-425) µm, ambient temperature of 34.5 °C and humidity 22% (Lab conditions).The results show that the material loss due to abrasive wear increased monotonically with the applied load at constant sliding speed and constant grit size due to increasing depth of penetration in both dry and wet sand which agrees with Archard´s equation. Sliding speed show insignificant effect on the wear loss of metals at constant load and constant grit size in both dry and wet sand. Wet sand results show higher wear losses than dry sand (20-70) % due to micro abrasion – corrosion wear and high slurry concentration.